2015
DOI: 10.1016/j.forsciint.2014.10.039
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between clothing and air weapon pellets

Abstract: Comparatively few studies have been carried out on air weapon injuries yet there are significant number of injuries and fatalities caused by these low power weapons because of their availability and the public perception that because they need no licence they are assumed to be safe. In this study ballistic gel was tested by Bloom and rupture tests to check on consistency of production. Two series of tests were carried out firing into unclothed gel blocks and blocks loosely covered by different items of clothin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
2
10
0
Order By: Relevance
“…The observation of loose fit clothing reducing the penetration capacity was similar to the results observed during the Wightman, Wark and Thomson [18] study with air rifle pellets.…”
Section: Fibre Structure and Level Of Penetrationsupporting
confidence: 88%
See 1 more Smart Citation
“…The observation of loose fit clothing reducing the penetration capacity was similar to the results observed during the Wightman, Wark and Thomson [18] study with air rifle pellets.…”
Section: Fibre Structure and Level Of Penetrationsupporting
confidence: 88%
“…Several studies have been carried out with regards to penetration capacity in firearms, air weapons and even bladed weapons. The Wightman, Wark and Thomson [18] study found that clothing that was in contact with the gelatine provided a reduced penetration capacity of various types of air rifle pellets, however, a greater relative standard deviation was found when the clothing was loosely wrapped around the gelatine. In the same study, it was also noted that any damage caused to clothing was dependent on the pellet shape, with the pointed pellets causing the least damage and the domed pellets causing the most damage.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…More recently published was a study that showed the presence of a layer of denim on a model of a deer femur embedded in 20% (by mass) gelatine led to an increase in the risk of indirect femoral fracture when shot by 5.56 NATO ammunition [ 22 ], followed by an increasing interest in examining clothing effects on wounding in ballistic research [e.g. 4 , 20 , 21 , 23 , 44 , 45 ]. Published research has demonstrated that intermediate layers (clothing or other personal protective equipment) can affect damage sustained by a gelatine block during ballistic testing [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of ballistic research tends to focus on the difference between the calibre rather than the difference between bullets. Wightman, Beard and Allison [17] looked into the difference between types of air rifle pellets and how they interacted with bone, then in 2015, Wightman, Wark and Thomson [18], investigated the interaction between air rifle pellets and clothing. This study aims to combine these two studies and determine the impact damage to bone by both round and flat nosed bullets and whether the introduction of fabrics, as well as a skin substitute, will have any effect on the penetration depth.…”
Section: Micro-ct Scannermentioning
confidence: 99%